Mathematical aspects of computer and information sciences : 6th International Conference, MACIS 2015, Berlin, Germany, November 11-13, 2015, Revised selected papers /: 6th International Conference, MACIS 2015, Berlin, Germany, November 11-13, 2015, Revised selected papers. (2016) - Unknown
No abstract available